Effect of collagen cross-linkers on dentin bond strength: A systematic review and network meta-analysis - Chen, Huan; Sun, Guangdi; Wang, Huimin; Yu, Shiyang; Tian, Zilu; Zhu, Song (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Objective: This study aimed to evaluate the role of collagen cross-linkers in the bonding performance of the resin-dentin interface through a systematic review and a network meta-analysis. Sources: The literature search was conducted in several databases like PubMed, EMBASE, Cochrane, Scopus and Web of Science from their inception till April 30, 2022. Study selection: The inclusion criteria consisted of in vitro studies evaluating the micro-tensile and micro-shear bond strengths of different cross-linkers acting on dentin. Bayesian network meta-analysis was conducted using RStudio. Data: Out of the 294 studies evaluated in the full-text analysis, 40 were included in the systematic review and meta-analysis. Most studies have used cross-linkers as primer (65.1%), followed by incorporating them into in adhesives and acid etching agents. The application methods of the adhesive system were classified as "etch-and-rinse (ER) adhesives"（77%） and "self-etching (SE) adhesives". Moreover, there were six types of cross-linkers in this presented review, of which the most numerous were polyphenols. Conclusion: Different application methods of cross-linkers, the long-term results showed that were only effective when used for longer durations, the immediate results were not statistically different. According to immediate and long-term results, etch-and-rinse (ER) adhesives showed a greater bonding performance than the control groups (p≤0.05), whereas self-etching (SE) adhesives showed similar bond strength values (p≥0.05). The result of network meta-analysis (NMA) showed that Dope like compound showed higher long-term bonding performance than other cross-linkers. Clinical significance: Long-term clinical studies may be needed to determine the effect of the cross-linkers on the bonding properties.